A framework for modeling bioimpedance measurements of nonhomogeneous tissues: a theoretical and simulation study. (17th June 2021) - Luo, Xuesong; Wang, Shaoping; Sanchez, Benjamin
Abstract: Objective. Bioimpedance technology is experiencing an increased use to assess health in a wide range of new consumer, research and clinical applications. However, the interaction between tissues producing bioimpedance data is often unclear. Methods. This work provides a novel theoretical framework to model bioimpedance measurements of nonhomogeneous tissues. We consider five case studies to validate the usefulness of our approach against finite element model simulations. Results. Theoretical and FEM-simulated apparent resistance and reactance data were in good agreement, with a maximum relative errors <4% and <8%, respectively. Conclusion. The biophysics-driven framework developed provides compact analytical expressions to model nonhomogeneous bioimpedance measurements including multiple tissues with arbitrary shape and electrical properties. This work provides a new perspective to interpret nonhomogeneous bioimpedance measurements using series, parallel, and series-parallel circuit-like topology equivalents. Significance. Our framework is a new tool to better understand and describe complex nonhomogeneous biological measurements as, for example, cardiac, brain and respiratory applications using (non)invasive electrodes.